High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life